Developing Interactive Smart Wheel Media to Enhance Conceptual Understanding of Matter State Changes in Elementary School Students - Syabrina Hayati Siregar; Andina Halimsyah Rambe (Journal of Social Work and Science Education, 2027)
Conceptual understanding is essential in elementary science, yet students often memorize the names of matter state changes without explaining the underlying processes. This study aimed to develop and evaluate Interactive Smart Wheel media for improving fourth-grade students’ conceptual understanding of matter state changes. Research and Development was conducted through the ADDIE stages of analysis, design, development, implementation, and evaluation. The local product trial involved 25 fourth-grade students, one classroom teacher, one media validator, and one subject-matter validator at SD Swasta IT Zia Salsabila. Data were collected through classroom observation, interviews, expert-validation sheets, teacher and student response questionnaires, and pretest-posttest concept-understanding tests. The media expert score was 95%, and the material expert score was 90%, indicating high validity. Teacher and student practicality scores were 95.8% and 85.4%, respectively. Students’ mean score increased from 42.8 on the pretest to 84.8 on the posttest, with a mean N-Gain of 0.748 in the high category. The study’s originality lies in combining a physical rotating wheel, visual representations, QR-linked videos, and quiz activities within one manipulative medium. Practically, the product offers teachers a structured way to transform abstract processes into visible and participatory learning experiences. The findings contribute preliminary evidence that interactive manipulative media can support conceptual understanding, although the small single-school sample limits generalization.